Effect of an Enhanced Recovery After Surgery Program on Opioid Use and Patient-Reported Outcomes. Issue 2 (August 2018) - Meyer, Larissa A.; Lasala, Javier; Iniesta, Maria D.; Nick, Alpa M.; Munsell, Mark F.; Shi, Qiuling; Wang, Xin Shelley; Cain, Katherine E.; Lu, Karen H.; Ramirez, Pedro T.
Abstract : OBJECTIVE: To investigate the effect of an enhanced recovery after surgery (ERAS) program on perioperative outcomes with an emphasis on opioid consumption and patient-reported outcomes in the immediate and extended postoperative periods. METHODS: We initiated our ERAS program as part of a quality improvement initiative in November 2014. We compared clinical outcomes among a cohort of 607 women undergoing open gynecologic surgery before or after implementation of ERAS. For 293 patients, patient-reported outcomes were compared using the MD Anderson Symptom Inventory-Ovarian Cancer. RESULTS: Median age was 58 years (range 18–85 years). Median length of stay decreased by 25% for patients in the ERAS pathway ( P <.001). Overall, patients in the ERAS group had a 72% reduction in median opioid consumption and 16% were opioid-free during admission up to postoperative day 3 ( P <.001). There was no difference in pain scores ( P =.80). Patients on ERAS reported less fatigue ( P =.01), interference with walking ( P =.003), and total interference (composite score of physical and affective measures) during hospitalization ( P =.008). After discharge, those on the ERAS pathway demonstrated a significantly shorter median time to return to no or mild fatigue (10 vs 30 days, P =.03), mild or no interference with walking (5 vs 13 days, P =.003), and mild to no total interference (3 vs 13 days, P =.02). There were no significant differences in complications, rates of readmission, or reoperation between the pre- and post-ERAS groups. CONCLUSION: Implementation of an ERAS program was associated with significantly decreased opioid use after surgery and improvement in key patient-reported outcomes associated with functional recovery after surgery without compromising pain scores. Abstract : Participation in an enhanced recovery program was associated with decreased intraoperative and postoperative opioid intake and improved functional recovery in the hospital and after discharge.